User Interface Experience Analysis of PMB Online Buddhi Dharma Using System Usability Scale - Junaedi; Ardiane Rossi Kurniawan Maranto; Maysha Permata Putri; Suwitno (bit-Tech, 2023)
In the era of advanced digital technologies, the admission process for new students (PMBs) has become a critical aspect of education. To streamline and expedite this process, educational institutions are increasingly utilizing online enrollment applications. One such application, PMB Online Buddhi Dharma, plays a crucial role in this context. However, the success of these applications is not solely determined by technical ease; user experience, particularly the User Interface (UI), plays a pivotal role in influencing user satisfaction and efficiency. This study employs the System Usability Scale (SUS) method to comprehensively analyze the UI of the PMB Online Buddhi Dharma application, providing insights into usability and user satisfaction. Drawing from previous studies utilizing SUS in similar contexts, the research aims to contribute to the development and enhancement of the application's UI. This research evaluates too the effectiveness of Buddhi Dharma University's PMB Online in meeting the digital registration needs of prospective students, emphasizing ease of use and user acceptance. Through the SUS method, the study assesses user satisfaction and ease of use, obtaining an average SUS score of 78 from 30 respondents. This score categorizes Buddhi Dharma University Online PMB as "good," indicating a commendable level of acceptance from users, predominantly prospective students. The research concludes with implications for the application's further improvement and development, emphasizing the importance of user-friendly interfaces in digital admission processes.